10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Background Maintenance hemodialysis (MHD) patients commonly exhibit persistent inflammation and malnutrition, which are strongly associated with poor clinical outcomes. Objective Aims to investigate the impact of three-month changes in body composition on clinical prognosis in MHD patients and explore whether baseline inflammatory and nutritional biomarkers are correlated with body composition alterations. Methods All patients received thrice-weekly hemodialysis sessions. Body composition assessments at baseline and three months were obtained from bioimpedance analysis results using Body Composition Monitor (BCM) under normal hydration conditions, with data retrieved from the hospital's bioimpedance database. Results Advanced age, reduced albumin and hemoglobin levels were associated with a significantly diminished 3-year cumulative survival rate relative to the control group. Reductions in body mass index(BMI), waist circumference, percentage of body fat (PBF), and visceral fat area (VFA) within 3 months conferred a higher 3-year mortality risk, whereas alterations in skeletal muscle mass (SMM) and fat-free mass (FFM) were not significantly linked to 3-year mortality.Baseline NLR were significantly negatively correlated with 3-month variations in SMM and FFM, whereas initial serum albumin, hemoglobin, and lymphocyte count showed significant positive correlations with concurrent changes in BMI、SMM, and FFM. No significant links were observed between baseline inflammatory/nutritional biochemical markers and 3-month shifts in adipose-associated body composition parameters (PBF, VFA, and waist circumference). Conclusion 3-month reductions in adipose body composition conferred a significantly higher 3-year mortality risk in MDH patients. Baseline inflammatory and nutritional biochemical indices were significantly associated with changes in 3-month non-adipose mass, but not with changes in adipose tissue. 3-month changes in adipose components may be the critical factor modulating 3-year survival in MHD patients.